2016
DOI: 10.1136/bmjopen-2015-009804
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study on parental pro-drinking practices and adolescent alcohol drinking in Hong Kong

Abstract: ObjectivesTo investigate the association between parental pro-drinking practices (PPDPs) and alcohol drinking in Hong Kong Chinese adolescents.DesignA cross-sectional study.Setting4 randomly selected secondary schools in Hong Kong.Participants1738 students (mean age 14.6 years ±2.0, boys 67.8%).Main outcome measuresDrinking status, drinking intention and exposure to 9 PPDPs (eg, seeing parents drunk, helping parents buy alcohol, encouraged to drink by parents) were reported by students. Logistic regression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies found that parental drinking was strongly associated with children's mental health problems, including depression and anxiety [9]. In Hong Kong (HK), a local study showed that exposure to parental prodrinking practices was common in Chinese adolescents [10]. Of 1,700 HK secondary students, 51.0% saw their parents drink at home, and 23% were asked by their parents to open drinking bottles [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies found that parental drinking was strongly associated with children's mental health problems, including depression and anxiety [9]. In Hong Kong (HK), a local study showed that exposure to parental prodrinking practices was common in Chinese adolescents [10]. Of 1,700 HK secondary students, 51.0% saw their parents drink at home, and 23% were asked by their parents to open drinking bottles [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong (HK), a local study showed that exposure to parental prodrinking practices was common in Chinese adolescents [10]. Of 1,700 HK secondary students, 51.0% saw their parents drink at home, and 23% were asked by their parents to open drinking bottles [10]. Children with drinking parents were more likely to have psychological distress because of the higher risk of suffering from verbal abuse and physical violence at home [11].…”
Section: Introductionmentioning
confidence: 99%